My "u" book - Moncure, Jane Belk.; Moncure, Jane Belk.; Peltier, Pam. (Elgin, Ill. : Child's World ; Chicago, Ill. : Distributed by Children's Press, 1984)
Little "u" fills her box with umbrellas and many other things that begin with the short letter "u".
Rev. ed. of: My "u" sound box. c1984.
Keywords: African Americans; Alphabet; Fiction; Fiction